Information system for nuclear material accounting and control - S. N. Sytova; A. P. Dunets; A. N. Kavalenka; S. V. Charapitsa (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
A brief description of information system for nuclear material accounting developed for the national regulator in the field of nuclear and radiation safety - the Department for Nuclear and Radiation Safety of the Ministry of Emergency Situations of the Republic of Belarus (Gosatomnadzor) is given. The information system is a part of the Intellectual information system of a Gosatomnadzor employee to ensure control (supervision) in the field of nuclear and radiation safety. It is developed on the basis of free software. The system has been implemented in Gosatomnadzor and at present in the Republic of Belarus all nuclear material accounting with reporting to the IAEA is carried out with its help. The system, in full compliance with the IAEA requirements, provides automatic generation with all the necessary calculations based on the input data of the following reporting documents: physical inventory listing, inventory change report, material balance report, textual report, General Ledger. All reports are fully consistent each with other. An efficient mechanism has been developed for importing and exporting data from / to the system according to formats of fixed and labelled Code 10 required by the IAEA. All logs of the system describing reports contain a field “IAEA approved” (yes / no). If it set to “yes”, they are closed for editing and correction. A special tool has been developed for making adjustments to these documents in accordance with the IAEA rules. The system contains fully completed reference books (small journals referenced by all major journals in the database) with the necessary reference data in accordance with Code 10. The information system meets all the IAEA requirements for such systems of national regulators in the field of accounting, control and supervision of nuclear material. It can be easily translated into other languages and adapted for the needs of accounting and control of nuclear material in operating organizations.